Design of highly sensitive refractive index biosensor with cobalt-glass materials for detection of glucose concentration in blood - Trupti Kamani; Shobhit K. Patel; Sana Ben Khalifa; Saleh Chebaane; Om Prakash Kumar; Ishwar Bhiradi; Ammar Armghan (Scientific Reports, 2025)
Abstract Diabetes represents a conceivably fatal condition that occurs because of elevated blood glucose levels. The surface plasmon resonance (SPR) biosensor has emerged as currently the most sophisticated method for determining glucose levels. The blood glucose biosensor performance is determined by the refraction coefficient of the substance containing glucose in the form of molecules. In this study, we have offered Hollow-Ring Cubic-Structured Refractive Index Biosensor (HRCSRIB) for monitoring glucose levels in blood from normal concentrations of 165 to 180 (mg/dL) in compared to diabetic glucose concentrations of 182, 205, 220, 240, 255, 289, 255 (mg/dL). This biosensor detects variations in the refractive index of urine, which correlate with changes in blood glucose concentration. The presented biosensing technology uses cobalt compounds and their unique structure to analyze blood glucose levels by measuring the urine refractive value. The study of various parameters associated with geometrical shape dimensions has been also represented. This offered biosensor has an exceptional sensitivity with 1750 nm/RIU, and a detection limit of 0.000410. The exceptional value of the quality factor, as well as the figure of merit value, is 1670.07 nm/RIU for 182 mg/dL and 1241.13 for 205–289 mg/dL respectively. The best transmittance response of 6%, 9%, 4%, and 32% has been obtained. The aforementioned sensor’s distinctive characteristics facilitate its biomedical applications as an optical on-chip sensor that monitors level of glucose.